The Death of the Da’i: The Autonomization of Religious Messages within Cyberspace - Fazlul Rahman (Ulumuna, 2018)
This paper attempts to explore the phenomenon of Islamic propagation (dakwah) on the Internet known as "e-dakwah." It problematizes the authority of religious messages within cyberspace vis a vis Internet’s anonymity. This 'cyber ethnographic' research shows that people in cyberscape are concerned more with the messages than their authors. This study confirms the autonomic truth of the messages as it is supported by Imam ‘Alī bin Abī Ṭālib’s popular argument “listen to what has been said, not who has said that." Consequently, the truth and acceptance of it in the dakwah activities or messages within cyberspace does not depend on the preachers (dā‘ī) and their professional capacity and intellectual knowledge, but on the object of dakwah (mad‘ū). This paper proposes the term “The death of the da’i,” which is adapted from Roland Barthes' term “The death of the author” in his image-music-text, to discuss the phenomenon.